2021
DOI: 10.1503/jpn.200032
|View full text |Cite
|
Sign up to set email alerts
|

Greater decision uncertainty characterizes a transdiagnostic patient sample during approach-avoidance conflict: a computational modelling approach

Abstract: Background: Imbalances in approach-avoidance conflict (AAC) decision-making (e.g., sacrificing rewards to avoid negative outcomes) are considered central to multiple psychiatric disorders. We used computational modelling to examine 2 factors that are often not distinguished in descriptive analyses of AAC: decision uncertainty and sensitivity to negative outcomes versus rewards (emotional conflict). Methods: A previously validated AAC task was completed by 478 participants, including healthy controls (n = 59),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 86 publications
4
37
0
Order By: Relevance
“…As such, if the semantics and functional role of desired outcomes is never inconsistent with the role of ( ), and the role of ( ) is always consistent with the semantics and functional role of desires, then active inference does effectively contain desired outcomes. This is consistent with recent empirical work that has used dAI to model behavior in reinforcement learning and reward-seeking tasks (Sajid, Ball, Parr, & Friston, 2021;Smith, Kirlic, et al, 2021;, and with other work demonstrating that dAI meets criteria for Bellman optimality (i.e., optimal reward-seeking within reinforcement learning) in certain limiting cases (Da Costa, Sajid, Parr, Friston, & Smith, 2020). In these cases, ( ) encodes the strength of the relative preferences for winning and losing money or points, being exposed to positive or negative emotional stimuli, and so forth.…”
Section: Desired Outcomes In Active Inferencesupporting
confidence: 88%
“…As such, if the semantics and functional role of desired outcomes is never inconsistent with the role of ( ), and the role of ( ) is always consistent with the semantics and functional role of desires, then active inference does effectively contain desired outcomes. This is consistent with recent empirical work that has used dAI to model behavior in reinforcement learning and reward-seeking tasks (Sajid, Ball, Parr, & Friston, 2021;Smith, Kirlic, et al, 2021;, and with other work demonstrating that dAI meets criteria for Bellman optimality (i.e., optimal reward-seeking within reinforcement learning) in certain limiting cases (Da Costa, Sajid, Parr, Friston, & Smith, 2020). In these cases, ( ) encodes the strength of the relative preferences for winning and losing money or points, being exposed to positive or negative emotional stimuli, and so forth.…”
Section: Desired Outcomes In Active Inferencesupporting
confidence: 88%
“…As such, if the semantics and functional role of desired outcomes are never inconsistent with the role of p(o τ ), and the role of p(o τ ) is always consistent with the semantics and functional role of desires, then active inference does effectively contain desired outcomes. This is consistent with recent empirical work that has used dAI to model behavior in reinforcement learning and reward-seeking tasks (Markovic et al, 2021;Sajid et al, 2021;Smith et al, 2020Smith et al, , 2021aSmith et al, , 2021b, and with other work demonstrating that dAI meets criteria for Bellman optimality (i.e., optimal reward-seeking within reinforcement learning) in certain limiting cases (Da Cost et al, 2020b). In these cases, p(o τ ) is used to encode the strength of the relative preferences for winning and losing money or points (e.g., subjective reward value), being exposed to positive or negative emotional stimuli, and so forth.…”
Section: Desired Outcomes In Active Inferencesupporting
confidence: 87%
“…In practice, several empirical studies have used model-fitting to identify the value of this precision in individual participants. For example, two studies in psychiatric samples fit this precision within the context of an approach-avoidance conflict task to identify differences in motivations to avoid exposure to unpleasant stimuli; and to identify continuous relationships between this precision and self-reported anxiety and decision uncertainty (Smith et al, 2021a(Smith et al, , 2021b. Two other studies in substance users identified individual differences in this precision value while participants performed a three-armed bandit task designed to examine the balance of information-versus reward-seeking behavior (Smith et al, 2020(Smith et al, , 2021c.…”
Section: The Motivational Force Of Desiresmentioning
confidence: 99%
“…The precision-driven active inference framework has been invoked in multiple transdiagnostic studies, including some published in JPN, 15,16 to explain abnormalities in perception, 17 interoception 18 and emotional expression, 19 to name a few. Here, we theoretically expand its application to disrupted communication in psychosis as a clinical phenomenon of interest.…”
Section: Precision-driven Active Inferencementioning
confidence: 99%